Clinical characteristics and risk factors associated with breakthrough varicella during varicella outbreaks - Wei Qin; Xiao-Kang Xu; Yao Wang; Xiang-Mei Meng; Cheng-Wu Yang; Feng Xia; Hong Su (Taylor & Francis Group, 2020)
Background Although a varicella vaccine has been available in China since 1998 in the private sector, varicella outbreaks and breakthrough varicella (BV) still occur. In 2018, four varicella outbreaks with high BV rate sequentially occurred in four schools in Lu'an, sparking local public health authority's concerns on the varicella vaccine. Therefore, we conducted this investigation to evaluate varicella vaccine effectiveness (VE), characterize BV, and detect potential risk factors associated with BV. Methods This was a three-stage study. First, a retrospective cohort study was done in each school to estimate the VEs of varicella vaccine  during outbreaks. Second, a descriptive epidemiological method was used to describe the characteristics of the four outbreaks and to compare the clinical characteristics between the BV cases and unvaccinated varicella cases. To identify the risk factors associated with BV, we conducted an unmatched case-control study in the third stage of the study. Results A total of 199 cases were identified among four outbreaks, and the overall attack rate was 14%. Of 1203 students with available vaccination information, 822 (68%) were vaccinated at least once. The overall VEs among four outbreaks ranged from 19% to 69%, whereas the VE against moderate or severe varicella ranged from 74% to 90%. Compared with unvaccinated varicella cases, the moderate or severe varicella (p < .001) and fever (p = .029) in the BV group were less common. Besides, BV cases had a shorter duration of disease (p = .007). Children vaccinated more than six years before the outbreak had a higher risk of developing BV compared with those vaccinated within the past six years (OR = 2.4, 95% CI: 1.2-4.8). The risk of developing BV differed by the exposure intensity. Compared with the presence of three or fewer varicella cases in the same class, the OR was 7.8 (95% CI: 3.6-16.9) for four to nine cases in the same class and 25.2 (95% CI: 13.5 -47.2) for that of 10 or more cases. Conclusions The overall VE was insufficient to protect varicella infection, and the VE for moderate or severe varicella was only moderate. The manifestations of BV cases were generally milder than those seen in natural varicella infection. The time since vaccination and the intensity of exposure are risk factors for developing BV during an outbreak.